Seroprevalence of Neospora caninum infection in cattle from Pereira, Colombia - Idarraga Bedoya, Samuel E. (2020)
There are over 25.6 million cattle heads in Colombia being the fourth-highest herd in Latin America. This study aimed to describe the seroprevalence of Neospora caninum in cattle from 25 rural farms at Pereira municipality, Risaralda Department, which has a total bovine population of 43,508 animals. A cross-sectional observational study was performed in beef and dairy herds during 2017–2018. A total of 325 animals in 25 herds, with 13 animals per herd, were sampled. A commercial competitive ELISA (cELISA) kit was used to detect N. caninum antibodies. Associated risk factors were analyzed in two different levels: individual animals and herds. For all the independent variables, chi-square (χ2) and Fisher tests were used to assess associations and significance. The overall estimated seropositivity was 20.6% (95%CI 16.2%–25.0%). The seroprevalence by herds was 92.0% ranging from 0.0% to 46.2%. Noteworthy, beef herds had significantly (p = 0.0107) higher seropositivity (50% of them above 35% of seropositivity) compared with those for milk purposes (4.8%) (OR = 20.0; 95%CI 1.2–331.0). Other risk factors were not significantly (p ≥ 0.05) associated with N. caninum seropositivity. Bovine neosporosis may be associated with abortions in both beef and dairy Colombian farms. More studies about the epidemiology, associated factors and consequences, as well as on tools for better diagnosis of bovine abortion, including histopathology and other ancillary tests, should be performed.